Intermediate microeconomics : price theory and applications - Ekelund, Robert B. (Robert Burton), 1940-; Ault, Richard (Lexington, Mass. : D.C. Heath, 1995)
Introduction to microeconomic theory. Theory of consumer behavior. The theory of the firm. Market structures. Resource markets. The role of government in markets and international trade.
Keywords: Microeconomics; Microeconomics